Mothering in the streets: Familial adaptation strategies of street‐identified Black American mothers - Hitchens, Brooklynn K.; Aviles, Ann M.; McCallops, Kathleen (Journal of marriage and family, 2022)
Objective Using components of the Family Adjustment and Adaptation Response Model, Critical Race Feminism, and Sites of Resilience, this study explored how street‐identified Black American mothers engage in street life, while juggling the pressures of childrearing, family, and home life within a distressed, urban Black community. Background Street‐identified Black American mothers are vilified for their intersecting identities of being Black women who are experiencing poverty, and who may also be involved in illegal activity. Black mothers are disproportionately represented in the criminal legal system, but existing research has inadequately examined how street‐identified Black mothers “do” family in the confines of structural violence. Method We addressed this gap by analyzing interview data with 39 street‐identified Black American mothers ages 18 to 54. Data were collected using street participatory action research. Results We identified a typology of three adaptive mothering strategies employed by street‐identified Black women as they respond to and cope with violent structural conditions shaping their mothering: constrained mothering, racialized mothering, and aspirational mothering. Conclusions Findings suggested that these strategies were developed in response to an overarching carceral apparatus, of which these mothers were tasked with avoiding when possible and confronting when necessary. Their mothering strategies were shaped by a collective, Black American cultural identity and worldview, and the mothers possessed a unique way of perceiving the world as criminalized subjects with disproportionate proximity to the punitive state.